Wilhelm Ebstein and the History of Surgery for Ebstein's Disease - Robicsek, Francis (The Thoracic and Cardiovascular Surgeon, 2013)
In the mirror of the life-story of Wilhelm Ebstein, the discovery of “Ebstein's Disease” is presented. The readers are guided through the individual stages of the development of surgical treatment of the condition.
Keywords: history; surgery/incisions; tricuspid valve; education; all levels; infant